Multi-scale, integrated approaches to understanding the nature and impact of past environmental and climatic change in the archaeological record, and the role of isotope zooarchaeology. (February 2019) - Jones, Jennifer; Britton, Kate
Abstract: Climatic change, and associated environmental changes, are key challenges facing the world today, and are altering the future of our planet and its inhabitants. Climatic and environmental shifts also had profound effects on human societies in the past, and archaeology has a key role in helping us understand how humans, animals and the broader ecosystem responds and adapts to environmental change. Understanding human-environmental interactions on local, regional, and global scales is therefore not only a key part of better understanding the past, but also for informing the present. A significant area to explore is the palaeoecology of archaeologically-important prey-species, both as a means of more accurately reconstructing ancient landscapes and ecosystems, but also for better understanding past human activity, landscape use and faunal resource exploitation. New biomolecular approaches, and particularly isotope zooarchaeology, have enhanced our ability to reconstruct past ecosystem dynamics, paleoenvironmental and paleoclimatic conditions, and the economic strategies that humans used to cope with them. However, the integration of multiple lines of evidence and methodologies remains the most powerful approach towards studying environmental change, resilience and adaptation in the past, not only for the benefit of archaeologists but other specialists. This special section of Journal of Archaeological Science Reports draws together papers using a range of methodologies to understand past human interactions with their environments, from Alaska, to Coastal Brazil, Europe and beyond. Studies are on a range of scales, from individual sites to big data, multi-site analyses, and encompass periods from Palaeolithic to the Middle Ages. Given the multi-faceted nature of the human past, archaeologists need to use a broad range of datasets to best understand environmental change and its impact on humans and animals. By drawing on inter-disciplinary specialisations and working alongside experts from other fields it will be possible to gain a more integrated and complete understanding of the ecological, economic, social and cultural effects of climatic and environmental changes on past populations. Highlights: Argues need for multiple methods in reconstructing human-environment interactions Emphasises faunal palaeoecology as part of living landscapes of the past Stresses role and cross-disciplinary value of isotope (zoo)archaeology Introduces research forming this special issue, and presents overview of papers Highlights value of archaeological record for other disciplines in integrated studies